PW 0276 Fatal drowning in the western cape province of south africa: a seven-year retrospective, epidemiological study. (November 2018) - Saunders, Colleen; Singh, Robyn; Simons, Abigail; Niekerk, Ashley van
Abstract : Drowning is a neglected public health threat in low- and middle-income countries where the greatest drowning burden is observed. Current trends in global drowning prevention are formulated from data in high-income countries and may not be appropriate in low-resource settings. However, there is a paucity of robust drowning surveillance data from low-resource settings, particularly in Africa. Understanding local epidemiological and risk factors will enable the development of context specific drowning prevention initiatives and the appropriate allocation of resources. The primary aim of this study was to describe the epidemiology of fatal drowning in the Western Cape province of South Africa between 2010 and 2016, in order to inform the development and evaluation of context-specific drowning prevention strategies in the Western Cape. This retrospective study describes the epidemiology of all fatal drowning incidents captured in the Western Cape vital registration system between 2010 and 2016. Fatal drowning data were obtained with approval from the Forensic Pathology Services of the Western Cape Government. A total of 1391 fatal drowning incidents occurred in the Western Cape between 2010 and 2016, equating to an age-adjusted drowning mortality rate of 3.25 per 100 000 population. Drowning mortality rates were four-fold higher in males compared to females, and highest in children less than 5 years of age. The findings presented here will allow for the development of evidence based drowning prevention interventions and informed decision making in the allocation of public health resources.